Development of severe skeletal defects in induced SHP-2-deficient adult mice: a model of skeletal malformation in humans with SHP-2 mutations - Timothy J. Bauler; Nobuhiro Kamiya; Philip E. Lapinski; Eric Langewisch; Yuji Mishina; John E. Wilkinson; Gen-Sheng Feng; Philip D. King (The Company of Biologists, 2011)
SUMMARY SHP-2 (encoded by PTPN11) is a ubiquitously expressed protein tyrosine phosphatase required for signal transduction by multiple different cell surface receptors. Humans with germline SHP-2 mutations develop Noonan syndrome or LEOPARD syndrome, which are characterized by cardiovascular, neurological and skeletal abnormalities. To study how SHP-2 regulates tissue homeostasis in normal adults, we used a conditional SHP-2 mouse mutant in which loss of expression of SHP-2 was induced in multiple tissues in response to drug administration. Induced deletion of SHP-2 resulted in impaired hematopoiesis, weight loss and lethality. Most strikingly, induced SHP-2-deficient mice developed severe skeletal abnormalities, including kyphoses and scolioses of the spine. Skeletal malformations were associated with alterations in cartilage and a marked increase in trabecular bone mass. Osteoclasts were essentially absent from the bones of SHP-2-deficient mice, thus accounting for the osteopetrotic phenotype. Studies in vitro revealed that osteoclastogenesis that was stimulated by macrophage colony-stimulating factor (M-CSF) and receptor activator of nuclear factor kappa B ligand (RANKL) was defective in SHP-2-deficient mice. At least in part, this was explained by a requirement for SHP-2 in M-CSF-induced activation of the pro-survival protein kinase AKT in hematopoietic precursor cells. These findings illustrate an essential role for SHP-2 in skeletal growth and remodeling in adults, and reveal some of the cellular and molecular mechanisms involved. The model is predicted to be of further use in understanding how SHP-2 regulates skeletal morphogenesis, which could lead to the development of novel therapies for the treatment of skeletal malformations in human patients with SHP-2 mutations.